Retroviral sero‐reactivity in LGL leukaemia patients and family members. (14th October 2019) - Nyland, Susan B.; Feith, David J.; Poss, Mary; Olson, Thomas L.; Krissinger, Daniel J.; Poiesz, Bernard J.; Ruscetti, Francis W.; Loughran, Thomas P.
Abstract: T‐cell large granular lymphocyte (T‐LGL) leukaemia is characterized by a clonal proliferation of cytotoxic T cells and is frequently associated with rheumatoid arthritis. Sera from some LGL leukaemia patients react to a portion of the human T‐cell leukaemia virus (HTLV‐1/2) transmembrane envelope protein, BA21, although HTLV‐1/2 infection is rare in LGL leukaemia patients. Here we show that family members, including spouses, of an LGL leukaemia patient had elevated LGL counts, BA21 reactivity and, additionally, recognition of HIV‐1 gp41. Thus, both LGL leukaemia patients and clinically normal contacts sharing the same environment have evidence of exposure to a retrovirus.